2019
DOI: 10.1101/819342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local auxin biosynthesis promotes shoot patterning and stem cell differentiation in Arabidopsis shoot apex

Abstract: One of the striking aspects of stem cells is their ability to self-renew to maintain the adequate pool over extended periods and differentiate into distinct cell types on demand to sustain the tissue growth and repair by supplying new cells. Arabidopsis plant harbors pluripotent stem cells in the central zone (CZ) of the shoot apex. The daughters of these cells upon cell division move towards the peripheral zone (PZ). At the flanks of the meristem, they form lateral organs. Cells that get displaced underneath … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Precise spatiotemporal local auxin biosynthesis within the IM and its polar transport and accumulation at specific sites from sources elsewhere in the plant are essential for FM initiation (Alvarez-Buylla et al 2010;Yadav et al 2019). This is evidenced by classical mutants, for example, in PIN-FORMED1 (PIN1), which encodes a polar auxin efflux carrier (Gälweiler et al 1998).…”
Section: Auxin Is Essential For Floral Meristem Initiationmentioning
confidence: 99%
“…Precise spatiotemporal local auxin biosynthesis within the IM and its polar transport and accumulation at specific sites from sources elsewhere in the plant are essential for FM initiation (Alvarez-Buylla et al 2010;Yadav et al 2019). This is evidenced by classical mutants, for example, in PIN-FORMED1 (PIN1), which encodes a polar auxin efflux carrier (Gälweiler et al 1998).…”
Section: Auxin Is Essential For Floral Meristem Initiationmentioning
confidence: 99%
“…Although thallus branching occurs by notch dichotomy, a type of apical branching that is developmentally distinct from gametophore branching 7,26 , Marchantia taa and yuc knock-down plants also display hyperbranching phenotypes. Beyond bryophytes, various studies in the flowering plant Arabidopsis thaliana have shown that AtTAA1/WEI8, AtTAR2, AtYUC1 , AtYUC4 and AtYUC6 genes are expressed in discrete and partially overlapping domains of the shoot apical meristem 14,15 . Double and triple mutants in these genes, including yuc1yuc4, yuc1yuc4yuc6 and taa1tar2 allele combinations, show various degrees of decreased apical dominance reflected by an enhanced production of branches.…”
Section: Discussionmentioning
confidence: 99%
“…Auxin is derived from tryptophan (TRP)-independent and dependent biosynthetic pathways 13 . In the latter, the dominant pathway in plants, TRP is converted to indole-3-pyruvic acid (IPyA) by TRYPTOPHAN AMINO-TRANSFERASE (TAA/TAR) enzymes, that is then converted to auxin by YUCCA FLAVIN MONOOXYGENASE-LIKE (YUC) enzymes [14][15][16][17] . Auxin metabolite profiling in PpTAR and PpYUC overexpression lines, and pptar mutants have suggested that both steps of auxin biosynthesis are essential and identified TRP-to-IPyA conversion as a rate-limiting step in P. patens 13,18,19 .…”
Section: Massive and Rapid Reprogramming Of Early Auxin-responsive Genes Follows Gametophore Decapitationmentioning
confidence: 99%
“…Imaging of the synthetic auxin response reporters, DR5::GFP and DII::Venus, at consecutive time points during flower development revealed that auxin response maxima in the floral meristem colocalize with the positions of organ initiation (Goldental-Cohen et al, 2017; van Mourik et al, 2012). Precise spatiotemporal local auxin biosynthesis and its polar transport are essential for floral meristem initiation and subsequent development (Alvarez-Buylla et al, 2010; Yadav et al, 2020).…”
Section: Introductionmentioning
confidence: 99%